A method for producing isoparaffin solvent oil
By using a fixed bed process and a combination reaction of the polymerization and hydrogenation of mesoporous ZSM-23 molecular sieve catalyst in the production of isomerial alkane solvent oil, the problems of raw material limitation, low production efficiency and environmental pollution in the prior art are solved, and the yield and isomerial branching of isomerial alkane solvent oil are improved.
Patent Information
- Application Number
- CN202210065662.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-20
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-01-20
AI Technical Summary
The existing isomer alkane solvent oil production methods have problems such as raw material limitations, low production efficiency, difficulty in product separation and environmental pollution, and the degree of isomer branching is low.
Low-carbon olefins are used as raw materials, and the polymerization and hydrogenation combination reaction is carried out through a fixed bed process, and mesoporous ZSM-23 molecular sieve and metal halide/Group Transition Metal Oxide are used as polymerization catalysts to improve the reaction activity and selectivity.
The yield, isomer alkane solvent oil, isomer alkane content and isomer branching degree are improved, impurity content and environmental pollution are reduced, and an efficient and environmentally friendly production process is achieved.
Smart Images

Figure CN116515528B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing isoparaffin solvent oil, and in particular to a method for producing isoparaffin solvent oil by using low-carbon olefins as raw materials through a polymerization and hydrogenation combined process. Background Art
[0002] As one of the five major categories of petroleum products, solvent oil has an increasing market demand. my country's fine chemicals, electronics industry, household products, and daily chemicals have also continuously improved their requirements for solvent performance. Foreign companies such as ExxonMobil, Idemitsu, Shell, and Total all have their own technical specifications for clean solvent oil products, and their products are serialized, which are divided into normal alkane solvent oil, cycloalkane solvent oil, and isoalkane solvent oil according to the hydrocarbon composition.
[0003] At present, isoparaffin solvent oil has the characteristics of being sulfur-free and aromatic-free, having little odor, low toxicity, good stability, good solubility, low freezing point and low surface tension. In addition, the relative inertness of the saturated isoparaffin structure can minimize or eliminate harmful reactions in industrial production processes and consumer applications. It is a very environmentally friendly high-end solvent oil and is widely used in washing daily chemicals, cosmetics, printing and dyeing diluents, ink solvents, metal processing cleaning agents, rust-proof oils, odorless sprays, odorless oil coatings, paints, organic sol formulas, advanced dry cleaning oils, etc.
[0004] At present, the production of isoparaffin solvent oil in China mainly uses isoparaffin and olefin as raw materials, and obtains isoparaffin solvent oil through alkylation reaction, hydrogenation and distillation. There are also isoparaffin solvent oils that are obtained by hydrogenation isomerization and alkane-olefin separation using FT synthetic oil as raw material. At present, foreign countries use synthetic processes to produce environmentally friendly isoparaffin solvent oils. The content of aromatic hydrocarbons and various impurities in the products is very low, which can reduce the odor of the solvent to an extremely low level or even odorless, and thus it is accepted by many industries that have demands for health and environmental protection. Compared with isoparaffin solvent oils produced by alkylation, hydrogenation isomerization, alkane-olefin separation and other processes, the synthetic process has a more ideal structural composition, higher purity of isoparaffins, no aromatic hydrocarbons, significant quality and performance advantages, and a large increase in product added value.
[0005] US5866748 discloses a method for producing isoparaffin solvent oil. The isoparaffin solvent oil is produced by using a hydrogenation isomerization method using a Fischer-Tropsch product of a C8-C20 fraction with a high content of normal alkanes as a raw material. This method uses the Fischer-Tropsch reaction product as a raw material, and has strict restrictions on the properties of the raw material. Only a specific fraction with a high content of normal alkanes can be used as a raw material, so the scope of technical application is limited. At the same time, the higher value olefins in the Fischer-Tropsch synthetic oil are wasted.
[0006] CN107312569A discloses a method for producing isoparaffin solvent oil from Fischer-Tropsch naphtha. Fischer-Tropsch naphtha is used as raw material, and alcohol dehydration reaction, polymerization reaction and hydrogenation reaction are carried out in Fischer-Tropsch naphtha in sequence to obtain isoparaffin solvent oil. The isoparaffin solvent oil obtained by the method has high yield and high purity. However, the method uses AlCl3 catalyst, has the problems of low production efficiency and difficulty in product separation, and aluminum chloride is highly corrosive, polluting the environment and corroding equipment.
[0007] CN104560193A discloses a method for preparing a lubricating base oil and / or solvent oil, wherein the polymerization raw material comprises olefins, alcohols and optional alkanes, wherein the content of α-olefins in the olefins is ≥ 85%, and through polymerization, hydrofining and / or hydroisomerization reaction, the fraction with an initial boiling point greater than 340°C in the obtained reaction product is used to obtain a lubricating base oil and / or a fraction with a final boiling point less than 340°C is used to obtain a solvent oil. However, this method requires a high content of α-olefins in the raw material, and the product is mainly composed of lubricating base oil, and a small amount of isoparaffin solvent oil is obtained, and the isoparaffin solvent oil has a low degree of isomeric branching. Summary of the invention
[0008] In order to overcome the shortcomings of the prior art, the present invention provides a method for producing isoparaffin solvent oil. The method adopts a fixed bed process and has the advantages of easy product separation and reduced environmental pollution. The obtained isoparaffin solvent oil has a high yield, high isoparaffin content, and high isomeric branching degree.
[0009] A method for producing isoparaffin solvent oil, the method comprising the following contents: low-carbon olefin raw materials enter a polymerization reaction zone for polymerization reaction; the materials after the polymerization reaction enter a hydrogenation refining reaction zone; the refined materials are separated to obtain isoparaffin solvent oil products of various fraction ranges;
[0010] The polymerization reaction zone is sequentially loaded with two polymerization catalysts along the material flow direction, wherein the first polymerization catalyst A is a mesoporous ZSM-23 molecular sieve or a formed mesoporous ZSM-23 molecular sieve; the second polymerization catalyst further contains a metal halide and / or a second polymerization catalyst compared to the first polymerization catalyst. Group transition metal oxides.
[0011] In the method of the present invention, the low-carbon olefin is a C2-C6 olefin, preferably a C4 and / or C5 olefin.
[0012] In the method of the present invention, the metal halide is AlCl3 or TiCl4, and based on the weight percentage of the final catalyst, the final catalyst contains 0.1wt% to 20wt% of the metal halide, preferably 1wt% to 15wt%; The transition metal of the first group is Fe, Co, or Ni. Based on the weight of the final catalyst, the catalyst contains The amount of the transition metal oxide is 1wt% to 35wt%, preferably 2wt% to 8wt%.
[0013] In the method of the present invention, the shape of the polymerization catalyst can be formed according to actual needs, such as a three-leaf clover shape, a four-leaf clover shape, a cylindrical strip shape or other suitable shapes.
[0014] In the method of the present invention, the two polymerization catalysts may be arranged in the same reactor, or in a plurality of separate reactors.
[0015] In the method of the present invention, the polymerization reaction zone and the hydrofining reaction zone may be arranged in the same reactor, or may be arranged in a plurality of separate reactors.
[0016] In the method of the present invention, the polymerization catalyst A is a mesoporous ZSM-23 molecular sieve, the pore size of the mesoporous ZSM-23 molecular sieve is 3-8nm, preferably 3-6nm, and the mesopore volume accounts for 45-90% of the total pore volume of the molecular sieve, preferably 50-85%, and further preferably 55-81%; the relative crystallinity of the mesoporous ZSM-23 molecular sieve is 95-120%, and the relative crystallinity retention of the molecular sieve after hydrothermal treatment with water vapor at 600°C for 2 hours is 95-100%.
[0017] In the method of the present invention, the polymerization catalyst A is a formed mesoporous ZSM-23 molecular sieve, wherein the mesoporous ZSM-23 molecular sieve in the polymerization catalyst is 30wt% to 90wt%, preferably 60wt% to 80wt%; the polymerization catalyst has the following properties: a specific surface area of 290-410m 2 / g, pore volume is 0.31-0.5cm 3 / g, micropore specific surface area is 50-160m 2 / g, mesopore specific surface area is 150-305m 2 / g; preferably, the specific surface area is 310-390m 2 / g, pore volume is 0.34-0.45cm 3 / g, micropore specific surface area is 70-130m 2 / g, mesopore specific surface area is 191-285m 2 / g.
[0018] In the method of the present invention, the hydrorefining reaction zone is loaded with a conventional hydrorefining catalyst in the art, which may be a non-precious metal hydrorefining catalyst or a precious metal hydrorefining catalyst. The present invention preferably uses a precious metal hydrorefining catalyst.
[0019] In the method of the present invention, the polymerization reaction conditions are: reaction temperature is 20-180°C, preferably 40-100°C, pressure is 0.1-10.0MPa, preferably 1.0MPa-5.0MPa, volume space velocity is 0.5h -1 ~5.0h -1 , preferably 0.8h -1 ~2.0 h -1 .
[0020] In the method of the present invention, the hydrofining reaction conditions are: reaction temperature is 120°C to 350°C, preferably 150°C to 300°C, reaction pressure is 3.0MPa to 12.0MPa, preferably 5.0MPa to 10.0MPa, volume space velocity is 0.5h -1 ~5.0 h -1 , preferably 0.8h -1 ~3.0 h -1 , the volume ratio of hydrogen to oil is 200:1~1500:1, preferably 600:1~1200:1.
[0021] A non-limiting preparation of a mesoporous ZSM-23 molecular sieve polymerization catalyst comprises the following steps:
[0022] a. preparing or selecting amorphous silicon dioxide;
[0023] b. treating amorphous silica with an alkali;
[0024] c Mesoporous ZSM-23 molecular sieve was prepared using alkali-treated amorphous silica as the silicon source.
[0025] In step a of the above method, the amorphous silicon dioxide has a specific surface area of 600-1300m 2 / g, preferably 700-1200m 2 / g; pore volume is 0.6-1.3cm 3 / g, preferably 0.7-1.2cm 3 / g; the pore diameter is 1-15nm, preferably 2-10nm.
[0026] In step a of the above method, the amorphous silica preparation process is as follows: adding a silicon source to deionized water and dispersing it evenly, then adding a surfactant and stirring; adjusting the solution pH to 1-5, preferably 1.5-4, and heating it in a water bath for a period of time; filtering, washing, drying, and calcining to obtain amorphous silica.
[0027] In the above method, during the preparation of amorphous silicon dioxide, the silicon source is an inorganic silicon source, preferably one or more of water glass, silica sol or white carbon black.
[0028] In the above method, during the preparation of amorphous silicon dioxide, the surfactant is one or more of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, and octadecyltrimethylammonium bromide.
[0029] In the above method, during the preparation of the amorphous silica, the molar ratio of the silicon source in terms of SiO2 to the surfactant is 1:(0.02-0.3), preferably 1:(0.05-0.2).
[0030] In the above method, during the preparation of the amorphous silicon dioxide, the molar ratio of the silicon source in terms of SiO2 to deionized water is 1:(30-300), preferably 1:(50-220).
[0031] In the above method, during the preparation of the amorphous silica, the heating temperature is 30-80°C, preferably 40-70°C, and the heating time is 0.5-8h, preferably 3-6h.
[0032] In step b of the above method, the alkali treatment is to add the amorphous silicon dioxide prepared in step a into an alkaline solution and heat and stir.
[0033] In the above method, the alkali treatment adopts inorganic alkali treatment, and the inorganic alkali is one or more of sodium hydroxide, potassium hydroxide or ammonia water.
[0034] In the above method, the alkali treatment heating and stirring time is 0.5-12h, preferably 2-8h; the heating temperature is 25-60°C, preferably 30-50°C.
[0035] In the above method, the molar ratio of amorphous silica calculated as SiO2 to the inorganic base is 0.05-0.24, preferably 0.06-0.22.
[0036] In step c of the above method, in preparing ZSM-23 molecular sieve using alkali-treated amorphous silicon dioxide as a silicon source, any method for preparing ZSM-23 molecular sieve known in the prior art may be used, and a method for preparing ZSM-23 molecular sieve that is not yet known in the prior art but will be known in the future may also be used. For example, a known method is disclosed in U.S. Pat. No. 4,990,342 of Mobil Oil Corporation.
[0037] In step c of the above method, preferably, alkali-treated amorphous silicon dioxide is used as a silicon source, and the silicon source is mixed with an aluminum source, an alkali source (MOH), a template (R), and water to form a gel, and the ZSM-23 molecular sieve is obtained after crystallization, filtration, washing, drying, and calcination;
[0038] More preferably, the molar ratio of silicon source (in terms of SiO2): aluminum source (in terms of Al2O3): alkali source (in terms of hydroxide): template: H2O in the gel is 1: (0.003-0.03): (0.03-0.3): (0.05-2): (10-90); further preferably, the molar ratio of silicon source (in terms of SiO2): aluminum source (in terms of Al2O3): alkali source (in terms of hydroxide): template: H2O in the gel is 1: (0.005-0.02): (0.03-0.16): (0.08-1.6): (20-70);
[0039] More preferably, the gel is crystallized at 150-200°C, preferably 170-180°C, for 24-96h, preferably 36-72h, and then filtered, washed, dried, and calcined to obtain a ZSM-23 molecular sieve;
[0040] More preferably, the drying temperature is 80-120° C., the drying time is 4-12 hours, the roasting temperature is 500-600° C., and the roasting time is 2-6 hours.
[0041] Another non-limiting method for preparing the polymerization catalyst A comprises the following steps: kneading the prepared mesoporous ZSM-23 molecular sieve with a binder and a peptizing agent, followed by drying and calcining to prepare a final molded ZSM-23 molecular sieve polymerization catalyst.
[0042] In the above method, the binder used can be small-pore alumina, the pore volume of the small-pore alumina used is 0.3-0.5 ml / g, and the specific surface area is 200-400 m 2 / g. The peptizing agent used can be one or more of aluminum sulfate, citric acid, nitric acid, acetic acid, oxalic acid, etc.
[0043] In the above method, the drying conditions are as follows: the drying temperature is 60°C to 180°C, preferably 90°C to 120°C, and the drying time is 0.5h to 20.0h, preferably 3.0h to 6.0h; the roasting conditions are as follows: the roasting temperature is 350°C to 750°C, preferably 500°C to 650°C, and the roasting time is 0.5h to 20.0h, preferably 3.0h to 6.0h. The drying and roasting can be carried out in an oxygen-containing atmosphere, with no particular restriction on the oxygen concentration, such as air atmosphere, etc., or in an inert atmosphere, such as nitrogen atmosphere, etc.
[0044] A non-limiting method for preparing a polymerization catalyst is as follows: a metal halide and / or a first catalyst is introduced into the prepared formed mesoporous ZSM-23 molecular sieve; The transition metal oxide of the first group is dried and calcined to obtain a metal halide and / or the first group transition metal oxide. Group transition metal oxide polymerization catalysts.
[0045] Compared with the prior art, the method for synthesizing isoparaffin solvent oil of the present invention has the following advantages:
[0046] (1) The method of the present invention uses a polymerization catalyst containing mesoporous ZSM-23. The polymerization catalyst containing mesoporous ZSM-23 is graded and loaded, which improves the selectivity of olefin polymerization and further improves the polymerization reaction activity, reduces the reaction temperature, and improves the raw material conversion rate;
[0047] (2) The present invention adopts a fixed bed synthesis and hydrogenation combined process, which solves the problems of corrosion of traditional low-carbon olefin polymerization reaction equipment, high chlorine content of products, and environmental pollution caused by catalyst post-treatment. The polymerized olefin product is easier to separate and can directly enter the hydrogenation reaction zone;
[0048] (3) The synthetic isoparaffin solvent oil obtained by the present invention has many isomeric branches, concentrated carbon numbers, extremely low impurities, no aromatic hydrocarbons, and an isoparaffin content of >99%. DETAILED DESCRIPTION
[0049] The analysis method of the present invention is as follows: The specific surface area and pore volume of the catalyst or molecular sieve are measured by using an ASAP 2405 physical adsorption instrument from Micromeritics, USA, where the specific surface area refers to the sum of the micropore specific surface area and the mesopore specific surface area. The loaded metal content is measured by atomic absorption spectroscopy.
[0050] The XRD spectrum of the sample was obtained by a Dmax2500 X-ray diffractometer produced by Rigaku Corporation of Japan, and the relative crystallinity of the sample was calculated. The sum of the heights of the diffraction peaks at 2θ of about 11.3 and 19.5-23° in the XRD spectrum of conventional ZSM-23 molecular sieve was taken as 100% crystallinity, and the relative crystallinity of other samples was obtained by comparison.
[0051] The specific preparation method of the polymerization catalyst A in the method of the present invention is as follows:
[0052] (1) Preparation of mesoporous ZSM-23 molecular sieve;
[0053] Add 50g of water glass (SiO2 mass fraction is 27%) to 250g of deionized water, stir and disperse evenly, then add octadecyl trimethyl ammonium chloride (C 18 TMAC1) was stirred for 0.5h, wherein SiO2 and C 18 The molar ratio of TMACl is 1:0.08; the solution pH is adjusted to 2 with hydrochloric acid, and then placed in a 50°C water bath and heated for 4 hours; after completion, the solution is filtered, washed, dried at 100°C for 4 hours, and calcined at 550°C for 3 hours to obtain amorphous silica;
[0054] Dissolve 0.42 g of NaOH in 40 mL of deionized water, add 3.7 g of the prepared mesoporous silicon source, and stir in a 35 ° C water bath for 6 h;
[0055] Aluminum sulfate and isopropylamine (IPA) were dissolved in the remaining water in sequence, and then added to the silicon source dispersion to obtain a total molar ratio of SiO2 in the silicon source: Al2O3 in the aluminum source: OH - :IPA:H2O=1:0.005:0.10:1.0:50 gel was crystallized at 180°C for 48h, filtered, washed, dried and calcined to obtain ZSM-23 molecular sieve. The properties of the molecular sieve are as follows: The specific surface area of the molecular sieve is 387m 2 / g, pore volume is 0.41cm 3 / g, micropore specific surface area is 99m 2 / g, mesopore specific surface area is 288m 2 / g, the mesopore content with a pore size of 3-8nm is 56%, the relative crystallinity is 104%, and the relative crystallinity after hydrothermal treatment is 102%.
[0056] (2) Preparation of catalyst
[0057] The ZSM-23 molecular sieve, small pore alumina and nitric acid were mixed and formed, and then dried at 120°C for 8 hours and calcined at 600°C for 4 hours to prepare the catalyst. The small pore alumina used has a pore volume of 0.5 ml / g and a specific surface area of 300 m 2 / g.
[0058] Through analytical characterization, the specific surface area of the catalyst is 335m 2 / g, pore volume is 0.48cm 3 / g, micropore specific surface area is 80m 2 / g, mesopore specific surface area is 255m 2 / g, the catalyst contains 75wt% ZSM-23 molecular sieve.
[0059] The preparation method of olefin polymerization catalyst B in the method of the present invention is as follows:
[0060] The ZSM-23 molecular sieve, small pore alumina and binder in olefin polymerization catalyst A were mechanically mixed and formed, and then dried at 120°C for 8 hours and calcined at 600°C for 4 hours to prepare a catalyst carrier. The small pore alumina used had a pore volume of 0.5 ml / g and a specific surface area of 300 m 2 / g.
[0061] 300 g of the carrier was added to 1.0 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 3 h, and then vacuum dried at 70° C. for 3 h. Then, calcined at 500° C. for 8 h.
[0062] Through analysis and characterization, the specific surface area of the catalyst is 305m 2 / g, pore volume is 0.43cm 3 / g, micropore specific surface area is 75m 2 / g, mesopore specific surface area is 230m 2 / g. The iron oxide content in the catalyst is 3.55 wt%, and the mass content of ZSM-23 molecular sieve is 67.5%.
[0063] The preparation method of olefin polymerization catalyst C in the method of the present invention is as follows:
[0064] 300 g of the carrier in Catalyst B was added to 1.5 M ferric nitrate solution, stirred evenly, soaked at 30° C. for 5 h, and then vacuum dried at 70° C. for 3 h. Then, calcined at 500° C. for 8 h.
[0065] Through analytical characterization, the specific surface area of the catalyst is 299m 2 / g, pore volume is 0.42cm 3 / g, micropore specific surface area is 71m 2 / g, mesopore specific surface area is 228m 2 / g. The iron oxide content in the catalyst is 5.26 wt%, and the mass content of ZSM-23 molecular sieve is 66.2%.
[0066] The preparation method of olefin polymerization catalyst D in the method of the present invention is as follows:
[0067] 300 g of the carrier in Catalyst B was added to 1.0 M nickel nitrate solution, stirred evenly, soaked at 30°C for 6 hours, and then vacuum dried at 80°C for 3 hours. Then, calcined at 500°C for 8 hours.
[0068] Through analysis and characterization, the specific surface area of the catalyst is 303m 2 / g, pore volume is 0.43cm 3 / g, micropore specific surface area is 73m 2 / g, mesopore specific surface area is 230m 2 / g. The nickel oxide content in the catalyst is 2.32 wt%, and the mass content of ZSM-23 molecular sieve is 66.2%.
[0069] The preparation method of olefin polymerization catalyst E in the method of the present invention is as follows:
[0070] 300 g of the carrier in Catalyst B was added to 1.0 M ferric nitrate solution, stirred evenly, soaked at 30°C for 3 hours, and then vacuum dried at 70°C for 3 hours. Then, calcined at 500°C for 8 hours.
[0071] 40g of anhydrous aluminum chloride was dissolved in 2000ml of tetrahydrofuran, and then 50g of the support was mixed with the solution and kept at reflux temperature for 12h. Finally, the supported catalyst was dried at 120°C in vacuum for 6h to obtain the supported catalyst.
[0072] Through analytical characterization, the specific surface area of the catalyst is 298m 2 / g, pore volume is 0.43cm 3 / g, micropore specific surface area is 73m 2 / g, mesopore specific surface area is 225m 2 / g. The composition of the catalyst is as follows: the content of aluminum chloride in the supported catalyst is 3.50wt%, the content of iron oxide in the catalyst is 3.55wt%, and the mass content of ZSM-23 molecular sieve is 65.3%.
[0073] The hydrogenation refining catalyst in the method of the present invention can be prepared according to the method described in CN103769194A, using amorphous silicon aluminum and SBA-15 / Y composite molecular sieve as carriers to prepare a catalyst containing 0.1wt% to 0.5wt% of Pt and 0.3wt% to 0.8wt% of Pd, and the specific surface area of the catalyst is 380 to 500m 2 / g, and the pore volume is 0.6~0.9ml / g.
[0074] In order to better illustrate the present invention, the following is further described in conjunction with examples, but the present invention is not limited to these examples. The physicochemical properties of the olefin polymerization catalyst and the hydrorefining catalyst of the present invention are shown in Tables 1 and 2.
[0075] Table 1. Physicochemical properties of olefin polymerization catalysts
[0076]
[0077] Table 2. Physicochemical properties of hydrorefining catalysts
[0078]
[0079] Embodiment 1:
[0080] Isobutylene was used as the raw material. The properties of the raw material are shown in Table 3. The synthesis reaction zone used the combination of catalyst A and catalyst B in Table 1. The ratio of catalyst A to catalyst B was 3:1. The reaction conditions in the synthesis reaction zone were a volume space velocity of 1.0 h -1 The reaction temperature is 60°C and the pressure is 3.0MPa. The catalyst in Table 2 is used in the hydrogenation refining reaction zone. The reaction conditions are the reaction temperature is 190°C and the volume space velocity is 1.0h -1 , pressure is 6.0MPa, and hydrogen-oil volume ratio is 1000:1. The process conditions and results are shown in Table 4.
[0081] Embodiment 2:
[0082] Using isobutylene as raw material, the synthesis reaction zone uses the combination of catalyst A and catalyst C in Table 1, the ratio of catalyst A to catalyst C is 3:1, and the reaction conditions in the synthesis reaction zone are a volume space velocity of 1.0h -1 The reaction temperature is 30°C and the pressure is 3.0 MPa. The catalyst in Table 2 is used in the hydrogenation refining reaction zone. The reaction conditions are the reaction temperature is 190°C and the volume space velocity is 1.0 h -1 , pressure is 6.0MPa, and hydrogen-oil volume ratio is 1000:1. The process conditions and results are shown in Table 4.
[0083] Embodiment 3:
[0084] Using isobutylene as raw material, the synthesis reaction zone uses a combination of catalyst A and catalyst D in Table 1, the ratio of catalyst A to catalyst D is 3:1, and the reaction conditions in the synthesis reaction zone are a volume space velocity of 1.0h -1 The reaction temperature is 60°C and the pressure is 2.0 MPa. The catalyst in Table 2 is used in the hydrogenation refining reaction zone. The reaction conditions are the reaction temperature is 190°C and the volume space velocity is 1.0 h -1 , pressure is 6.0MPa, and hydrogen-oil volume ratio is 1000:1. The process conditions and results are shown in Table 4.
[0085] Embodiment 4:
[0086] Using isobutylene as raw material, the synthesis reaction zone uses the combination of catalyst A and catalyst E in Table 1, the ratio of catalyst A to catalyst E is 3:1, and the reaction conditions in the synthesis reaction zone are a volume space velocity of 1.0h -1 The reaction temperature is 60°C and the pressure is 2.0 MPa. The catalyst in Table 2 is used in the hydrogenation refining reaction zone. The reaction conditions are the reaction temperature is 190°C and the volume space velocity is 1.0 h -1 , pressure is 6.0MPa, and hydrogen-oil volume ratio is 1000:1. The process conditions and results are shown in Table 4.
[0087] Embodiment 5:
[0088] Using isobutylene as raw material, the synthesis reaction zone uses the combination of catalyst A and catalyst E in Table 1, the ratio of catalyst A to catalyst E is 3:1, and the reaction conditions in the synthesis reaction zone are a volume space velocity of 1.0h -1 The reaction temperature is 40°C and the pressure is 2.0 MPa. The catalyst in Table 2 is used in the hydrogenation refining reaction zone. The reaction conditions are the reaction temperature is 190°C and the volume space velocity is 1.0 h -1 , pressure is 6.0MPa, and hydrogen-oil volume ratio is 1000:1. The process conditions and results are shown in Table 4.
[0089] Comparative Example
[0090] Isobutylene was used as raw material, conventional anhydrous AlCl3 was selected as a synthesis catalyst, and the synthesis reaction was carried out in a reactor, the catalyst addition amount was 3%, the reaction temperature was 60°C, the reaction pressure was 2.0Mpa, and the reaction time was 2h. The synthesized product was subjected to fixed bed hydrorefining to obtain isoparaffin solvent oil, and the hydrogenation process conditions were the same as those in Example 1. The process conditions and results are shown in Table 4.
[0091] Table 3. Isobutylene raw material properties
[0092]
[0093] Table 4 Process conditions and results of examples and comparative examples
[0094]
Claims
1. A method for producing isoparaffin solvent oil, characterized in that: The method comprises the following contents: low-carbon olefin raw materials enter a polymerization reaction zone for polymerization reaction; the materials after polymerization reaction enter a hydrogenation refining reaction zone; the refined materials are separated to obtain isoparaffin solvent oil products of various fraction ranges; Wherein, the polymerization reaction zone is sequentially loaded with two polymerization catalysts along the material flow direction, the first polymerization catalyst A is a mesoporous ZSM-23 molecular sieve or a formed mesoporous ZSM-23 molecular sieve; the second polymerization catalyst further contains a metal halide and / or a Group VIII transition metal oxide compared to the first polymerization catalyst; the metal halide is AlCl3 or TiCl4, and based on the weight percentage of the final catalyst, the final catalyst contains 0.1wt%~20wt% of the metal halide; the Group VIII transition metal is Fe, Co, or Ni, and based on the weight of the final catalyst, the catalyst contains 1wt%~35wt% of the Group VIII transition metal oxide.
2. The method according to claim 1, characterized in that: The low carbon olefin is a C2-C6 olefin.
3. The method according to claim 2, characterized in that: The low carbon olefins are C4 and / or C5 olefins.
4. The method according to claim 1, characterized in that: Based on the weight percentage of the final catalyst, the final catalyst contains 1wt% to 15wt% of metal halide.
5. The method according to claim 1, characterized in that: Based on the weight of the final catalyst, the catalyst contains 2wt% to 8wt% of the Group VIII transition metal oxide.
6. The method according to claim 1, characterized in that: The polymerization catalyst is in the shape of a three-leaf clover, a four-leaf clover or a cylindrical strip.
7. The method according to claim 1, characterized in that: The two polymerization catalysts are arranged in the same reactor, or in a plurality of separate reactors.
8. The method according to claim 1, characterized in that: The polymerization reaction zone and the hydrofining reaction zone are arranged in the same reactor or in a plurality of separate reactors.
9. The method according to claim 1, characterized in that: The polymerization catalyst A is a mesoporous ZSM-23 molecular sieve, the pore size of the mesoporous ZSM-23 molecular sieve is 3-8nm; the relative crystallinity of the mesoporous ZSM-23 molecular sieve is 95-120%, and the relative crystallinity retention of the molecular sieve after hydrothermal treatment with water vapor at 600°C for 2 hours is 95-100%.
10. The method according to claim 1, characterized in that: The polymerization catalyst A is a mesoporous ZSM-23 molecular sieve, and the pore volume of mesopores with a diameter of 3-6 nm accounts for 45-90% of the total pore volume of the molecular sieve.
11. The method according to claim 1, characterized in that: The polymerization catalyst A is a mesoporous ZSM-23 molecular sieve, and the pore volume of mesopores with a diameter of 3-6 nm accounts for 50-85% of the total pore volume of the molecular sieve.
12. The method according to claim 1, characterized in that: The polymerization catalyst A is a mesoporous ZSM-23 molecular sieve, and the pore volume of mesopores with a diameter of 3-6 nm accounts for 55-81% of the total pore volume of the molecular sieve.
13. The method according to claim 1, characterized in that: The polymerization catalyst A is a formed mesoporous ZSM-23 molecular sieve, wherein the mesoporous ZSM-23 molecular sieve in the polymerization catalyst is 30wt% to 90wt%; the polymerization catalyst has the following properties: a specific surface area of 290-410m 2 / g, pore volume is 0.31-0.5cm 3 / g, micropore specific surface area is 50-160m 2 / g, mesopore specific surface area is 150-305m 2 / gg.
14. The method according to claim 13, characterized in that: The mesoporous ZSM-23 molecular sieve in the polymerization catalyst is 60wt% to 80wt%; the polymerization catalyst has the following properties: a specific surface area of 310-390m 2 / g, pore volume is 0.34-0.45cm 3 / g, micropore specific surface area is 70-130m 2 / g, mesopore specific surface area is 191-285m 2 / g.
15. The method according to claim 1, characterized in that: The polymerization reaction conditions are: reaction temperature 20~180℃, pressure 0.1~10.0MPa, volume space velocity 0.5~5.0h -1 ; The hydrofining reaction conditions are: reaction temperature is 120℃~350℃, reaction pressure is 3.0MPa~12.0MPa, volume space velocity is 0.5h -1 ~5.0 h -1 The volume ratio of hydrogen to oil is 200:1~1500:
1.
16. The method according to claim 15, characterized in that: The polymerization conditions are: reaction temperature 40℃~100℃, pressure 1.0MPa~5.0MPa, volume space velocity 0.8h -1 ~2.0 h -1 ; The hydrofining reaction conditions are: reaction temperature is 150℃~300℃, reaction pressure is 5.0MPa~10.0MPa, volume space velocity is 0.8h -1 ~3.0 h -1 , the volume ratio of hydrogen to oil is 600:1~1200:1.
Citation Information
Patent Citations
Hydro-dearomatization catalyst and preparation method thereof
CN103769194A
Preparation method of base oil and / or solvent oil of lubricating oil
CN104560193A
Method for producing isoparaffin solvent oil from Fischer-Tropsch synthesis naphtha, and isoparaffin solvent oil obtained through method
CN107312569A
Fungicidal composition with synergistic activity
US4990342A
Hydroisomerization of a predominantly N-paraffin feed to produce high purity solvent compositions
US5866748A